2012
DOI: 10.1016/j.carbpol.2011.08.040
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between κ-carrageenan and chitosan in nanolayered coatings—Structural and transport properties

Abstract: The interactions between-carrageenan and chitosan, two oppositely charged polysaccharides, have been investigated through microcalorimetric and quartz crystal microbalance measurements. Microcalorimetric measurements show that-carrageenan/chitosan interaction is an exothermic process and that the alternate deposition of-carrageenan and chitosan results in the formation of a nanolayered coating mainly due to the electrostatic interactions existing between the two polyelectrolytes (though other types of interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 37 publications
6
30
0
1
Order By: Relevance
“…Table 3 shows the permeabilities to oxygen and water vapor of conventional and nano-laminate coatings. It is suggested that barrier properties of nano-laminate coatings are improved due to their nano-structure, which has an increased tortuosity resulting from the electrostatic interactions between the nano-laminate's components and also from the interpenetration of the successively deposited layers that hampers gas molecules migration through the structure [61,79,94]. The application of LbL technique in fruits and vegetables is very recent, and few studies showed its effect on shelf-life parameters.…”
Section: Emerging Technologies: Development Of Nanolaminate Coatingsmentioning
confidence: 99%
“…Table 3 shows the permeabilities to oxygen and water vapor of conventional and nano-laminate coatings. It is suggested that barrier properties of nano-laminate coatings are improved due to their nano-structure, which has an increased tortuosity resulting from the electrostatic interactions between the nano-laminate's components and also from the interpenetration of the successively deposited layers that hampers gas molecules migration through the structure [61,79,94]. The application of LbL technique in fruits and vegetables is very recent, and few studies showed its effect on shelf-life parameters.…”
Section: Emerging Technologies: Development Of Nanolaminate Coatingsmentioning
confidence: 99%
“…In one recent work published by Pinheiro et al, κ-carrageenan (polyanion) and chitosan (polycation) were applied onto aminated PET resulting in improved gas barrier properties (reduced oxygen and water vapor transmission rates) [74]. In other work presented by Carneiro-da-Cunha et al [75], alginate was employed as the polyanion, suggesting it as an attractive alternative as there was not significant difference in water vapor permeability between the aminated PET film used and its coated counterpart.…”
Section: Antimicrobialmentioning
confidence: 99%
“…Another technique with great potential in the development of nanoscopically structured new materials is the sequential LbL adsorption of polymer of solid substrates (Pinheiro et al, 2012;Weis et al, 2006). By means of this procedure, several biopolymers with opposite charges can be used to produce nanolayered films assembled through LbL.…”
Section: Nanostructured Biopolymer Layers For Food Packaging 21 Imprmentioning
confidence: 99%